2018
DOI: 10.15587/1729-4061.2018.139418
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the effect of nanoparticle additives to the refrigerant r141b on the pool boiling process

Abstract: Наведено результати експериментального дослiдження внутрiшнiх характеристик процесу кипiння у вiльному об'ємi холодоагенту R141b, розчину R141b/поверхнево-активна речовина Span-80 i нанофлюїду R141b/Span-80/наночастинки TiO 2 на поверхнях з нержавкої сталi й тефлону. Вимiри вiдривного дiаметра бульбашок, частоти вiдриву бульбашок та густини центрiв зародкоутворення проведено при атмосферному тиску в дiапазонi густини теплового потоку вiд 3,0 до 7,5 кВт•м-2. Дослiдження показали, що вiдривний дiаметр бульбашок … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Khliyeva et al [13] experimentally studied the impact of nanoparticle added substances to the refrigerant R141b on the pool boiling process. They observed that TiO2 nanoparticles additives to the R141b / Span-80 solution contributed to a 2-8-fold reduction in the amount of nucleation sites.…”
Section: Nanofluids Enhancement On Boilingmentioning
confidence: 99%
“…Khliyeva et al [13] experimentally studied the impact of nanoparticle added substances to the refrigerant R141b on the pool boiling process. They observed that TiO2 nanoparticles additives to the R141b / Span-80 solution contributed to a 2-8-fold reduction in the amount of nucleation sites.…”
Section: Nanofluids Enhancement On Boilingmentioning
confidence: 99%
“…The R141b refrigerant was chosen as the base fluid for the model system in this study. This refrigerant has been widely used for model studies by many researchers [3,10,12,13,20,21]. The nanorefrigerant preparation has not been difficult because R141b has the low vapor pressure at ambient temperatures.…”
Section: Justification Of the Selection Of The Objects Of Study Andmentioning
confidence: 99%
“…In addition, information on the thermophysical properties of the R141b/TiO 2 nanorefrigerant is necessary for the thermodynamic interpretation of previously obtained data on the boiling processes of this nanofluid [20,21]. The effects obtained in the study of the thermophysical properties of the model system R141b/nanoparticles can be extended to other halogenated hydrocarbons refrigerants, which are widely used in the refrigeration industry and in air conditioning systems.…”
Section: Justification Of the Selection Of The Objects Of Study Andmentioning
confidence: 99%
See 2 more Smart Citations